Writing for theatre : creative and critical approaches - Wiltshire, Kim (Approaches to writing, 2016)
"Writing for theatre is a unique art form, different even from other kinds of scriptwriting. Making theatre is a truly collaborative process which can be a tricky aspect to grasp when starting out. This book will take you on a journey from the origins of theatre to what it means to write for the stage today. It includes a series of interviews with writers, directors and dramaturgs, all of whom are making theatre now, providing an unrivalled glimpse into the world of contemporary theatre making. Kim Wiltshire explores the foundations, traits and skills necessary for playwriting alongside the creative possibilities of writing theatre in the digital age. Each part of the book ends with a series of exercises which students of the craft can use to practise their art and stretch their creativity"--